DETERMINATION OF COOLANT OPTIMUM OPERATING TEMPERATURE IN INJECTION PRINTING PROCESS BASED ON PRODUCT PRECISION LEVEL - Sati, Olivia Laras; Intang, Ambo; Saputra, Dendi Dwi (AUSTENIT, 2022)
Currently, plastic is more dominantly used because it is cheap, elastic and easy to process. To maintain the quality of plastic products, especially the type of Polyethylene Terephthalate (PET), the researchers implemented a modern plastic manufacturing system, namely using an injection molding system. In order to be able to meet the demands in solving problems that may arise in the process of making plastic products such as: quality, manufacturing time, and safety systems. The injection molding method replaces the old method, namely the hand press machine. This selection is based on advantages such as the consistency of the product produced because it is programmed, equipped with a control system, shorter product time, adequate security system, and other advantages. In this research, an experiment will be conducted to determine the optimum cooling temperature in the form of Pet Gallon. The problems that often occur are product defects due to shrinkage. In connection with this, the test results are obtained as follows: there is a difference in the shrinkage of product dimensions in the experiment using Cooled Chiller and Tower Chiller cooling, cooling has the greatest influence on the processing time of product manufacture, the optimum cooling temperature occurs at a cooling temperature of 200C.